2017
DOI: 10.22522/cmr20170121
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Astroturf Lobbying for Trust and Authenticity. Findings and Implications from an Experiment

Abstract: In contrast to authentic grassroots activism, in astroturfing, lobbyists sponsor an interest group that pretends to be a grassroots movement. In a vignette-based experiment, we investigate for the first time how astroturfing, compared to grassroots lobbying, reflects on stakeholders' perceptions of organizational trust and authenticity, how perceived frequency of the practices relates to them, and the associations they trigger. Our results indicate that stakeholders perceive an astroturfing organization as bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The good relations mentioned in the introduction can also involve an element of trust-the coping mechanism used when sufficient information or expertise is lacking but a decision needs to be made (Siegrist and Cvetkovich 2000). Should for instance lobbyists be trusted when they run Astroturf campaigns, advocate self-regulation or engage in the phenomenon of 'revolving doors' (Holman and Luneburg 2012;Lock and Seele 2017;Ron and Singer 2019)? Trust involves a moral dimension, but should not be confused with trustworthiness (Hardin 1996(Hardin , 2002.…”
Section: Theorymentioning
confidence: 99%
“…The good relations mentioned in the introduction can also involve an element of trust-the coping mechanism used when sufficient information or expertise is lacking but a decision needs to be made (Siegrist and Cvetkovich 2000). Should for instance lobbyists be trusted when they run Astroturf campaigns, advocate self-regulation or engage in the phenomenon of 'revolving doors' (Holman and Luneburg 2012;Lock and Seele 2017;Ron and Singer 2019)? Trust involves a moral dimension, but should not be confused with trustworthiness (Hardin 1996(Hardin , 2002.…”
Section: Theorymentioning
confidence: 99%
“…What these campaigns share is an outsized presence of external patrons, a linked advocacy group that presents itself as largely independent, and some exposure taking place that makes outside audiences question that apparent independence. While it is quite likely and expected that exposures would lead many public audiences to discredit the revealed front group and sponsor (Lock and Seele 2017; Pfau et al 2007), what is less clear is whether this affects public trust in advocacy groups writ large. For this, our analytic expectations rely upon prior research on categorical stigmatization processes, to which we turn next.…”
Section: Trust In Advocacy Groupsmentioning
confidence: 99%
“…In our case, we expect (and hypothesize below) that the disclosure that a low-reputation organization was orchestrating an astroturf campaign should be more harmful than a similar disclosure regarding a high-reputation sponsor, because observers will assume that such practices are more widespread than the case at hand, and that unsavory (and less trustworthy) actors are often behind them. Although other studies have shown that the revelation of front-group strategies generates significant reputational fallout (Lock and Seele 2017; Pfau et al 2007), our study is the first to examine how organizational reputations may shape overall perceptions of trust in advocacy groups; this is important conceptually because it provides an understanding of an additional layer of “guilt by association” effects (e.g., Pontikes, Negro, and Rao 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Enrichment : Public affairs practice is at its core about managing relationships (Fleisher, ) that are composed of various sequences of interpersonal, interorganizational, and organization‐public communication (Ledingham, ). Actors in public affairs such as lobbyists have a strategic goal they try to pursue through communication (Lock & Seele, ). Thus, it is only consistent to study public affairs cases also based on theoretical findings and perspectives from strategic communication research, or, more broadly, communication science, because public affairs relies on effective communication (Harris & Fleisher, ).…”
Section: Rigor In Case Study Researchmentioning
confidence: 99%